Literature Review: The Advantages of Bonding Attachment to Prevent Baby Blues in Post Partum Moms - Resky Salsasisca Sephianti; Herry Susanto; Sri Wahyuni; Nopi Nur Khasanah (GLOBAL HEALTH SCIENCE GROUP, 2025)
The postpartum period is a transitional period that is physically and emotionally challenging for a mother. One of the emotional disorders that often appear during this period is baby blues, which is a feeling of sadness, anxiety, and irritability that usually occurs in the first week after childbirth. This study aims to identify and analyze the benefits of bounding attachment in preventing baby blues in postpartum mothers through a systematic review of scientific literature. This study used a Systematic Literature Review design with reference to the PRISMA guidelines. Article searches were conducted through two main databases, namely PubMed and Google Scholar, with a publication range between 2020 and 2025. The search strategy was organized based on the PICO approach, using keywords such as